Baiting not-owned dogs against Echinococcus granulosus: innovative tools for integrated control - Elena Ciccone; Antonio Bosco; Paola Pepe; Martina Nocerino; Nicola Lattero; Gerald Umhang; Laatamna AbdElkarim; Samia Lahmar; Yousra Said; Giorgio Saralli; Giuseppe Piegari; Maria Chiara Alterisio; et al. (Parasitology, 2024)
Cystic echinococcosis (CE), caused by the larval stage of the cestode Echinococcus granulosus, is one of the most widespread zoonoses in Mediterranean countries. Baiting not-owned dogs with praziquantel (PZQ), due to their key role in the maintaining the transmission of CE, currently appears to be the most effective way to limit the transmission of CE, as well as an important aspect to introduce for the control of this parasitic disease. Therefore, this study aims to test 3 types of PZQ-based baits by evaluating different parameters (integrity over time, attractiveness and palatability for dogs, and mechanical resistance after release to different altitudes) and the bait acceptance in field by target animals, i.e. not-owned dogs, by using camera traps. The double PZQ-laced baits (with a double layer of highly palatable chews) showed the greatest resistance in the environment while also preserving the attractiveness and palatability up to 10 days, also withstood heights of 25 m, thus resulting as the most suitable also for drone delivery. The results on the field showed that most of the baits were consumed by not-owned dogs (82.2%), while the remaining were consumed by wild boars (8.9%), foxes (6.7%), badgers (1.1%) and hedgehogs (1.1%), confirming the specific and high attractiveness of the double PZQ-laced baits for the target population and highlights how an anthelmintic baiting programme may be a viable tool for the management of E. granulosus among free-ranging dog populations in endemic rural areas.